Current progress on in vitro differentiation of ovarian follicles from pluripotent stem cells - Wu, Genie Min Ju; Chen, Andy Chun Hang; Yeung, William Shu Biu; Lee, Yin Lau (Frontiers in Cell and Developmental Biology, 2023)
Mammalian female reproduction requires a functional ovary. Competence of the ovary is determined by the quality of its basic unit – ovarian follicles. A normal follicle consists of an oocyte enclosed within ovarian follicular cells. In humans and mice, the ovarian follicles are formed at the foetal and the early neonatal stage respectively, and their renewal at the adult stage is controversial. Extensive research emerges recently to produce ovarian follicles in-vitro from different species. Previous reports demonstrated the differentiation of mouse and human pluripotent stem cells into germline cells, termed primordial germ cell-like cells (PGCLCs). The germ cell-specific gene expressions and epigenetic features including global DNA demethylation and histone modifications of the pluripotent stem cells-derived PGCLCs were extensively characterized. The PGCLCs hold potential for forming ovarian follicles or organoids upon cocultured with ovarian somatic cells. Intriguingly, the oocytes isolated from the organoids could be fertilized in-vitro. Based on the knowledge of in-vivo derived pre-granulosa cells, the generation of these cells from pluripotent stem cells termed foetal ovarian somatic cell-like cells was also reported recently. Despite successful in-vitro folliculogenesis from pluripotent stem cells, the efficiency remains low, mainly due to the lack of information on the interaction between PGCLCs and pre-granulosa cells. The establishment of in-vitro pluripotent stem cell-based models paves the way for understanding the critical signalling pathways and molecules during folliculogenesis. This article aims to review the developmental events during in-vivo follicular development and discuss the current progress of generation of PGCLCs, pre-granulosa and theca cells in vitro.